Universos de alteridad en Henri de Régnier: Venecia y el mar Mediterráneo - Cabello, Nuria (Anales de Filología Francesa, 2018)
Henri de Régnier, man of the north, apparently cold and distant, he discovers, mesmerised, the beauty and exoticism of the Mediterranean scenery in 1904, on board of the luxurious yacht “Le Velléda”. The impact this trip caused in the author was long-lasting, so much so that in 1906, he embarks again on another Mediterranean cruise, this time on board of the yacht “Nirvana”, repeating almost the first itinerary port by port. During these journeys, Régnier takes careful note of his impressions on some travel notebooks. These notes will be used later by him to publish several works. Although Régnier was fascinated by the Mediterranean, it was Venice –the city he discovers in 1899– the place which awakened in him an intoxicating passion. From that moment on, the life and the work of Régnier reveal the perfume of Venice. Space of ambiguity, of Canals, of reflections and of masks, it is the ideal framework for the meeting with the otherness.